Ang tunay na lalaki ay ___ subverting the toxic masculinity of young FIlipino men and teen subcultures similar to those bred by the Pastor Hokage Bible study groups - Molintas, Isis Vonne R.; Ilagan, Joy M. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
In July 2017, the Filipino public was shocked by revelations of the rapid and widespread growth of "Pastor Hokage Bible Study Groups" (PHBSG) - groups curated by young Filipino men, using Facebook as a platform, and formed around sharing and bonding over sexually explicit material.

PHBSGs are any of at least 80 secret online groups that first sprung up as a way to circumvent the blocking of porn sites by Internet service providers and office IT administrators, but quickly evolved into an online social movement-of-sorts, a full-fledged subculture, with its own language, its own codes, and its own personalities.

Group activities revolve around posting, sharing, commenting and ultimately bonding over sexual content. Content ranges from slightly racey photographs to downright pornographic material, mostly shared without the consent or even knowledge of the subjects - all of whom are exclusively female. Some content involves revenge porn and, at the very worse, the subjects are underage girls.

Outraged, a number of women's groups, including a Facebook-based group called Catcalled in the Philippines, reported these PHBSG's activities and soon enough, many of these groups' FB pages were closed down. However, the movement itself simply went underground, where it continues to thrive. Members have adapted guerilla-like tactics, "closing shop", disappearing from their old site, lurking, then surfacing and reconvening under a new group, sometimes using other platforms, such as Reddit.

Does the Internet somehow promote these PHBSGs, revenge porn and other forms of toxic masculinity among young Filipino men and teens? Conversely, can the Internet be used to counteract these and promote an alternative positive masculinity?
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Includes bibliographical references
Keywords: Machismo -- Philippines; Image-based sexual abuse -- Philippines; Sexual harassment of women -- Philippines; Men -- Identity -- Philippines